Biocontrol practitioners’ perspectives on emerging genetic-based technologies for weed management - M. A. Rafter; N. Kumaran; D. R. Brookes; M. K. Reid; K. E. Bowers; A. J. McConnachie; M. Cristofaro; R. F. H. Sforza; B. Gooden; M. Hopper (BioControl, 2026)
Weed biocontrol researchers have been at the forefront of developing management solutions for invasive weeds for over 100 years and have a unique perspective to offer on the emerging field of genetic-based technologies such as gene drive and RNAi. As part of the XVI International Symposium on Biological Control of Weeds in May 2023 we conducted a focus group discussion workshop to explore biocontrol practitioners’ perspectives related to: (1) Genetic-based control technologies, and the factors influencing support (or not) for their application to weed management, especially weed biocontrol, (2) perceived opportunities to apply genetic-based control tools to enhance or complement weed biocontrol, focusing on whether/how genetic tools can be applied to fundamentally change the practice of weed biocontrol, and (3) genetic-based control in weed management and how it can operate within the Access and Benefit Sharing regulatory landscape. We analyse the perspectives of biocontrol scientists from the workshop and discuss the prospects and challenges of integrating novel genetic-based control tools with weed biocontrol.